2015
DOI: 10.1038/nm.3760
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal FXR agonism promotes adipose tissue browning and reduces obesity and insulin resistance

Abstract: The systemic expression of the bile acid (BA) sensor farnesoid X receptor (FXR) has led to promising new therapies targeting cholesterol metabolism, triglyceride production, hepatic steatosis and biliary cholestasis. In contrast to systemic therapy, bile acid release during a meal selectively activates intestinal FXR. By mimicking this tissue-selective effect, the gut-restricted FXR agonist fexaramine (Fex) robustly induces enteric fibroblast growth factor 15 (FGF15), leading to alterations in BA composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
554
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 616 publications
(584 citation statements)
references
References 49 publications
(53 reference statements)
21
554
3
6
Order By: Relevance
“…The LXR reduces Th17 lineage differentiation (46), as this effect competes with endogenous oxysterol ligands for RORγt (47) while gut-specific targeting of the FXR exerts antiinflammatory effects (48). A fat-enriched diet also reduces the number of ileal IL-17/RORγt CD4 + T cells, and IL-17/RORγt-deficient T cells are associated with the induction of glucose intolerance and obesity (49).…”
Section: Microbial and Dietary Influences On Intestinal Immunitymentioning
confidence: 99%
“…The LXR reduces Th17 lineage differentiation (46), as this effect competes with endogenous oxysterol ligands for RORγt (47) while gut-specific targeting of the FXR exerts antiinflammatory effects (48). A fat-enriched diet also reduces the number of ileal IL-17/RORγt CD4 + T cells, and IL-17/RORγt-deficient T cells are associated with the induction of glucose intolerance and obesity (49).…”
Section: Microbial and Dietary Influences On Intestinal Immunitymentioning
confidence: 99%
“…They showed that a deficiency of 12 α-hydroxylated bile acids and their synthetic enzyme CYP8B1 hinder the triglyceride, lowering effects of FXR. More recently, Fang et al [14] have shown that the bile acid release during a meal activates intestinal FXR. Up-regulating FXR with an intestinal agonist reduced diet-induced weight gain and hepatic glucose production while enhancing thermogenesis and browning of white adipose tissue.…”
Section: Bile Acid-activated Receptorsmentioning
confidence: 99%
“…Bile acids are increased after bariatric surgery, but not after a hypocaloric diet [31] . The exciting work by Fang et al [14] shows that the bile acid release during a meal selectively activates the intestinal FXR. They showed that the intestinal FXR agonist fexaramine induces FGF 15, leading to alterations in bile acid composition, reduced diet-induced weight gain, and hepatic glucose production, while enhancing thermogenesis and browning of white adipose tissue.…”
Section: The Forkhead Box Proteins (Foxo)mentioning
confidence: 99%
“…Recently, the gut-restricted FXR agonist fexaramine has been reported to reduce obesity and insulin resistance in mice. These effects are associated with browning of adipose tissue [84], which raises the possibility that fexaramine increases sympathetic activity.…”
Section: Mimicry Of Bariatric Surgerymentioning
confidence: 99%